Glass forming ability and continuous-cooling-transformation (CCT) diagrams of Vitreloy 105 as function of cooling rate and oxygen concentration - Campos Neto, N. D.; Soares, C.; Pereira, F. S.; Bergamaschi, V.; Antonio, S. G. [UNESP]; Kaufman, M. J.; Oliveira, M. F. de (Elsevier B.V., 2020)
A design of experiments was used to investigate the effects of oxygen concentrations and cooling rates during solidification of Vitreloy 105. The cooling rates of different copper molds were estimated by measuring the interlamellar spacing of an Al-33Cu (wt.%) eutectic alloy cast into these molds. Rietveld refinements of synchrotron X-ray diffraction (XRD) patterns were used to identify and quantify the phases and the results were used to construct a phase map for the Vitreloy 105. Differential scanning calorimetry (DSC) was used to determine the glass stability, transformation temperatures and to quantify the amorphous fractions. Amorphous quantification by image analysis in light optical microscopy (LOM) micrographs was performed in the same samples for comparison. Finally, continuous-cooling-transformation diagrams for Vitreloy 105, with different oxygen contents, were attempted for the first time.
Keywords: Bulk metallic glass; Oxygen; Cooling rate; Synchrotron x-ray diffraction; Continuous-cooling-transformation diagram